Pengembangan Model Komunikasi dalam Pemberdayaan Masyarakat Tani (Studi Kasus pada Kelompok Tani Jamur Merang Lestari Makmur di Desa Argorejo, Sedayu, Bantul) - Indardi Indardi (AGRARIS: Journal of Agribusiness and Rural Development Research, 2016)
The aims of this study were to portrait and understand a communication model for farmer community empowerment in the field and development efforts for the success of the farming community in the future. This study use constructivistic qualitative-interpretive paradigm. By understanding the phenomena that occur in the communication process in Lestari Makmur mushroom farmer group, identify important categories and construct as a portrait communication model. Based on the portrait of communication model, researchers tried to find alternative communication model for the future successfully of the farmer groups. This study has found an early model, which describes a communication model of mushroom farmer community empowerment that tend to be authoritarian. The leader of the farmer groups dominate in many things. It has been found two alternative community empowerment communication model: 1) Communication model of farmer community empowerment with the professional assistance, 2) Communication model of farmer community empowerment  with democratic leadership. It was concluded that the communication model of empowerment should be directed at the professional assistance, and for the future sustainability of the group, they are directed at the communication model with democratic leadership. It is important to  suggest to the farmer groups about the substantive of community empowerment, to understand on a mushroom farmer groups that responsibility is not only the cultivation of course, there are still many things to be done as a group of farmers to be more advanced in the future.